The Impact of Transformational Leadership on Employee Performance and Job Satisfaction - Gde Bayu Surya Parwita; Hermin Nainggolan; Noorhani Dyani Laksmi; Ilyas (Journal Management & Economics Review (JUMPER), 2026)
This study aims to examine the impact of creativity, market orientation, and competitive strategy on startup performance. In This study aims to examine the impact of transformational leadership on employee performance and job satisfaction, as well as the mediating role of job satisfaction in the relationship between transformational leadership and employee performance. A quantitative research approach with a causal design was employed, and data were collected from 200 employees using a structured questionnaire based on a five-point Likert scale. The data were analyzed using Structural Equation Modeling with the Partial Least Squares (SEM-PLS) method. The results indicate that transformational leadership has a positive and significant effect on employee performance and job satisfaction. Furthermore, job satisfaction is found to have a significant positive effect on employee performance. The mediation analysis reveals that job satisfaction partially mediates the relationship between transformational leadership and employee performance, indicating that transformational leadership enhances performance both directly and indirectly through improving employee satisfaction. These findings highlight the importance of transformational leadership in fostering a supportive work environment that enhances employee attitudes and performance outcomes. The study provides practical implications for organizations to invest in leadership development programs and improve job satisfaction to achieve sustainable organizational performance.